2014
DOI: 10.1080/01457632.2015.954947
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Mitigating Biofouling by Promoting Online Cleaning Using a Sacrificial Paraffin Coating

Abstract: The presence of biofouling layers on heat transfer surfaces can reduce heat transfer efficiency markedly. A new method for inhibiting biofouling growth and promoting rapid online cleaning for heat exchangers recovering thermal energy from treated sewage streams based on a temporary coating is reported. A paraffin wax coating is cast in place without needing to disassemble the device, while the low roughness and the hydrophobicity of the coating inhibit bacterial growth. The coating and any attached biofouling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Previous studies [11,41] have shown that the thermal resistance of the biofilms were linearly correlated with the biofilm thickness and the wet weight. In this study, the thermal resistance is of the main interest and the wet weight of the biofilms, instead of the cell count or the dry biomass, was measured.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies [11,41] have shown that the thermal resistance of the biofilms were linearly correlated with the biofilm thickness and the wet weight. In this study, the thermal resistance is of the main interest and the wet weight of the biofilms, instead of the cell count or the dry biomass, was measured.…”
Section: Discussionmentioning
confidence: 99%
“…However, the high bacterial concentration and the rich nutrient environment in the treated sewage cause biofilm formation on the stainless steel plates in the plate heat exchangers [9][10][11], which are important components in the TSSHPS to transfer heat from the treated sewage to the clean working medium due to their compactness and high thermal efficiency [12]. Biofilms reduce the heat transfer coefficient of the heat exchangers and the coefficient of performance of the whole heat pump system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation